PENGARUH MOTIVASI, DISIPLIN DAN LINGKUNGAN KERJA TERHADAP KINERJA PEGAWAI PADA ( PD. BPR BANK DAERAH PATI ) - Emalia Amik Nur Hidayah, 14.05.51.0269; Waruwu, Penunjang (Students' Journal of Economic and Management, 2019)
This study analyzed the effect of motivation, work discipline, and work environment on employee performance. Object of study in this paper is the PD. BPR Bank Daerah Pati . The sampling technique in this research is to use simple random sampling (random) sample of 60 respondents as data collection method using a questionnaire (questionnaire) by distributing a list of questions to the respondent in order to obtain information. The data were analyzed using factor analysis to test the validity of the question item, cronbach alpha formula to test the reliability of each of the independent variables were tested by regression analysis. The result showed that the motivationhas a positive effect and significant to the employee performance, work disciplinehas a positive effect and significant to the employee performance, andwork environment has a positive effect and significant to the employee performance.